In vitro evaluation of the enzymatic activity profile of non-albicans Candida species isolated from patients with oral candidiasis with or without diabetes - Sanita, Paula Volpato [UNESP]; Zago, Chaiene Evelin [UNESP]; Oliveira Mima, Ewerton Garcia de [UNESP]; Pavarina, Ana Claudia [UNESP]; Jorge, Janaina Habib [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Elsevier B.V., 2014)
Objective. To evaluate the expression of phospholipase (PL) and secreted aspartyl proteinase (SAP) by Candida glabrata and C tropicalis obtained from the denture biofilms of healthy participants (16 isolates), patients with oral candidiasis with diabetes (10 isolates), and patients with oral candidiasis without diabetes (25 isolates).Study Design. After incubation, the supernatants and pellets of the isolates were used for the enzymatic assays and quantification of colony-forming units (CFU), respectively. Colorimetric tests were used with phosphatidylcholine as a substrate for PL and azocasein as a substrate for SAP, and the absorbances of the samples were measured. Enzymatic rates were calculated, and values were normalized by CFU. Results were analyzed with factorial analyses of variance (alpha = .05).Results. C tropicalis and C glabrata were proteolytic and phospholipolytic. The clinical sources of isolates had no significant effect on the enzymatic activities (P > .05). C tropicalis had significantly higher enzymatic activity for both PL and SAP (P < .001) than did C glabrata.Conclusions. C tropicalis isolates produced significantly higher amounts of both enzymes than did the C glabrata isolates.